Peningkatan Hasil Belajar Tematik Terpadu Peserta Didik Menggunakan Model Problem-Based Learning di Kelas V Sekolah Dasar - Sari, Novita; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
The purpose of this study is to explain the improvement of student learning outcomes in integrated thematic learning elementary schools. This research is a Classroom Action Research (CAR) with qualitative and quantitative approaches. CAR is an action carried out by the teacher or together (collaboration) in the class by designing, implementing, observing and reflecting on actions using several cycles in a collaborative and participatory manner with the aim of improving and enhancing the quality of the learning process in the class. The research subject was 24 teachers and students at SDN 03 Padang Marapalam, Lengayang District, Pesisir Selatan Regency, consisting of 14 male students and 10 female students. Student learning outcomes can increase if learning uses the PBL model, this situation can be seen from the results of observing the Learning Implementation Plan (RPP) in cycle I 86.11% increasing to 94.44% in cycle II. In the results of observing the implementation of learning, the percentage for observing teacher activity in the first cycle was 80.36%, increasing to 92.85% in the second cycle. Based on the observations of students in the first cycle, 80.36% increased to 92.85% in the second cycle.